Temporal changes in the incidence and predictors of severe hypoglycaemia in type 2 diabetes: The Fremantle Diabetes Study - Davis, T.; Bruce, D.; Finn, Judith; Curtis, B.; Barraclough, H.; Davis, W. (2018)
Aim: To determine the incidence of severe hypoglycaemia and its predictors in community-based patients with type 2 diabetes studied between 2008 and 2013 compared with those in a cohort of patients with type 2 diabetes from the same geographical area assessed a decade earlier. Methods: We studied 1551 participants (mean age 65.7 years, 51.9% men) with type 2 diabetes from the longitudinal observational Fremantle Diabetes Study Phase II (FDS2). Severe hypoglycaemia was ascertained as that requiring ambulance attendance, emergency department services and/or hospitalization. Cox proportional hazards modelling was used to determine predictors of a first episode of severe hypoglycaemia, and negative binomial regression was used to identify predictors of frequency. Results: Sixty-three participants (4.1%) experienced 83 episodes, representing an incidence of 1.34/100 participant-years (95% confidence interval [CI] 1.08 to 1.67; vs 1.67/100 participant-years [95% CI 1.31-2.13] in the Fremantle Diabetes Study Phase I [FDS1]; P = 0.18). Those experiencing severe hypoglycaemia experienced one to four episodes in both cohorts. The independent predictors of incident severe hypoglycaemia in the FDS2 were: older age; higher educational attainment; alcohol consumption; current smoking; sulphonylurea/insulin treatment; prior severe hypoglycaemia; renal impairment; and plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP). The same variables except smoking were associated with frequency of severe hypoglycaemia. Most of these risk factors paralleled those in the FDS1, but current smoking and plasma NT-proBNP were novel. Conclusions: The incidence and frequency of severe hypoglycaemia did not change between the Fremantle Diabetes Study phases but novel risk factors, including plasma NT-proBNP, were observed in the FDS2.